Induced pluripotent stem cell line (INSAi001-A) from a Gaucher disease type 3 patient compound heterozygote for mutations in the GBA1 gene - Duarte, Ana Joana (2020)
Gaucher Disease (GD) type 3 is a neurological form of a multisystemic autosomal recessive disorder belonging to the group of lysosomal storage diseases. Causal mutations in the glucocerebrosidase 1 (GBA1) commonly lead to abnormal protein and GD, heterozygosity is a genetic risk factor for Parkinson's disease. This work describes the use of a non-integrative approach using Sendai Virus delivery to establish induced Pluripotent Stem Cells (iPSCs) from fibroblasts from a GD type 3 patient. Differentiation of iPSCs can be employed to generate a variety of complex cell types with a high degree of genetic complexity that would otherwise be unattainable.